The The Impact of the Benson Relaxation Technique in Alleviating Perineal Suture Pain Intensity in Postpartum Women - Solichah, Rismina; Rahmawati, Rahajeng Siti Nur; Wijayanti, Lumastari Ajeng (Jurnal Kesehatan, 2025)
Perineal rupture is a frequent obstetric complication that may occur during vaginal delivery, either spontaneously or with instrumental assistance. This condition often results in significant perineal pain, potentially hindering the physical recovery and psychological well-being of postpartum women. Non-pharmacological methods, such as Benson’s relaxation technique, have shown promise in managing pain effectively without the risks associated with pharmacological treatments. This quasi-experimental study aimed to examine the effectiveness of Benson’s relaxation technique in reducing perineal suture pain in postpartum women. The study involved 32 participants, with 16 women assigned to the experimental group and 16 to the control group. Pain intensity was measured using the Numeric Rating Scale (NRS), and the data were analyzed using the Wilcoxon Signed-Rank Test. Results revealed a statistically significant reduction in pain scores within the experimental group, with an Asymp. Sig. (2-tailed) value of 0.000, indicating a p-value well below the 0.05 threshold. These findings support the use of Benson’s relaxation technique as an effective non-pharmacological intervention for alleviating perineal pain. Integrating this method into postpartum care may enhance maternal comfort and expedite recovery, offering healthcare providers a practical and low-risk approach to pain management in clinical settings.